Perancangan Interior dan Stand Pempek Farina - Zhenita Andrelia (Intra, 2017)
Traditional foods are less appreciated nowadays by our people, many people are choosing foreign foods rather than traditional foods. Actually, traditional food has a great  potential for culinary business and it must be preserved. One of them is pempek which is a typical food of Palembang, which usually called pempek Palembang. Pempek Farina is a brand of pempek sellers who have many branches but unfortunately does not have the hallmark of interior design. For a place to eat, interior design is very important to attract customer's attention. Interior Planning and Pempek Farina Stand is a changes that we want to give to the Pempek Farina interior design. Therefore, Pempek Farina can has a characteristic that can be remembered and felt by visitors. This planning is based on the customers approach to Pempek Farina brand. Starting from the target of the customer, visitor habits, brand colors, etc. The existence of this interior design makes Pempek Farina has a standard in designing all the branches for uniform and in accordance with the standard owned. Moreover Pempek Farina has expanded into the franchise path.